Music in the Renaissance - Brown, Howard Mayer 1930-1993 (New Jersey Prentice Hall, 1976)
A history of Renaissance music focused on the music itself and the social and institutional contexts that shaped musical genres and performance. This book provides a complete overview of music in the 15th and 16th Centuries. It explains the most significant features of the music and the distinguishing characteristics of Renaissance composers (in Europe and the New World). It includes a large integrated anthology of 94 musical examples, as well as illustrations of musical instruments, notation, and ensembles.
Keywords: Renaissance (1400-1600); Music history